RESEARCH ON OCCUPATIONAL SAFETY CULTURE IN THE ENGINEERING INDUSTRY - ROMANISHINA , OLGA; LAVRENIUK, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Safety culture is a key factor that influences the success or failure of an organization. Institutions with a low level of safety culture or signs of dysfunction may recognize the need to implement corrective measures and seek recommendations for improvement. Therefore, the main objective of this work is to study how employees in the metalworking industry perceive safety culture using a safety climate assessment tool. The results obtained will serve as a basis for developing proposals aimed at improving working conditions and forming a stable and effective safety culture.As part of the study, respondents were asked to complete a questionnaire consisting of two parts: the first covered the demographic characteristics of the participants, and the second covered issues related to the safety climate. Seven key components were used to assess the level of safety culture: occupational safety management system and regulations, leadership and management involvement, attitude to safety, employee influence, employee participation, level of safety awareness, and appropriate behavior. The analysis of the results showed that employees positively assess the current safety management system, their own influence on processes, level of involvement, awareness, and behavioral aspects related to safety. At the same time, attitudes toward management were mostly critical—employees believe that management support for safety and health issues remains insufficient. As for the general attitude toward safety, it shows both positive and negative trends. But overall, the results of the study prove the importance of ongoing occupational safety training and awareness of employees on occupational safety culture and responsibility not only for their own lives and health, but also for the lives and health of other employees of the enterprise. A positive safety culture is the creation of an atmosphere in which employees are aware of the risks in their workplace, constantly beware of them and avoid any dangerous actions. A set of implemented factors, such as safety management procedures, management commitment, employee involvement, safety attitudes, peer influence, safety knowledge, and safe behavior, will lead to a reduction in the incidence of occupational injuries and occupational diseases at enterprises in the mechanical engineering industry.